Research on methods of working out seeding quantity of rice drill - ZHENG Yi-ping; HUA You-qing; LIN Jie; CHEM Li-neng (浙江大学学报. 农业与生命科学版)
In order to solve the difficult problems in detecting direct seeders' working state, the methods of counting seeds sowed non-singly by feed mechanism are researched. The innovation of the research is as follows: The relatively dense seeds flows are completely dispersed and a certain number of seeds are staggered from one another when passing the detection section by use of the tie-in of the transmitting tubes; then the detection section is divided into three detection areas, which results in sharp decrease of the chances that two or more seeds will pass the same detection section at a time; the infrared photo sensors and the detection circuit are employed to count the seeding number one area after another. The results of the experiment are as follows: (i) The leakage rate of seeding is 16.7 percent if the tie-in of the transmitting tube is not used. (ii) The leakage rate of seeding can be decreased to 6.81 percent if the tie-in of the transmitting tube is used and the detection is not conducted separately. (iii) The leakage rate of seeding can be decreased to 1.45 percent if the tie-in of the transmitting tube is used and the detection is conducted separately. Consequently, a way is worked out to detect the seeding quantity during the non-singly seeding process.